Millennials Intention to Use Health Smartwatches : Influence of Usefulness, Ease, Social Factors, and Awareness - Larasati, Tri Yuni; Harwani, Yuli (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Purpose – This study aims to identify the factors influencing the intention to use health-based smartwatches among millennials in the Jabodetabek area. The main focus is on the effects of perceived usefulness, perceived ease of use, and social influence, with sustainable health awareness as a mediating variable. Methodology/approach – This research employs a quantitative approach using an online survey distributed via Google Form to millennials who use health-based smartwatches in Indonesia, especially the Jabodetabek region. The data were analyzed using SmartPLS software version 4.1.1.2 to test the research model and hypotheses. Findings – The results show that perceived usefulness and sustainable health awareness have a significant influence on the intention to use health-based smartwatches. Furthermore, perceived usefulness, perceived ease of use, and social influence positively affect sustainable health awareness. Sustainable health awareness also serves as a partial mediator in the relationship between perceived usefulness and the intention to use health-based smartwatches. Novelty/value – This study contributes to the development of the Technology Acceptance Model (TAM) by incorporating sustainable health awareness as a mediating variable. The findings also offer practical insights for developers and marketers of wearable technology to enhance user adoption among millennials through beneficial, easy-to-use technology supported by positive social influence.